Determinan Faktor Risiko Neuropati Perifer Diabetik terhadap Kelembaban Kulit Kaki pada Pasien DM Tipe II - Gayatri, Ni Wayan Cening Setiari; Mertha, I Made; Suardana, I Ketut; Ngurah, I Gusti Ketut Gede (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2024)
Diabetic peripheral neuropathy is one of the chronic complications of DM which causes dysfunction of the peripheral nervous system, can occur in the autonomic nerves characterized by a decrease in foot skin moisture. This study aims to determine the determinants of diabetic peripheral neuropathy risk factors with foot skin moisture in type II DM patients The design of this research is non-experimental with a simple correlational method. The sample in this research is 35 respondents who were selected by consecutive sampling at the UPTD Puskesmas Ubud I. The results of the ordinal logistic regression statistical test obtained p-value of Model Fitting Information is 0,002 (p-value 0,05) and p-value Pseudo R-Square Negelkerke is 0,681, which means the risk factors of diabetic peripheral neuropathy (age, duration of diabetes mellitus, gender, transient blood glucose, total cholesterol, waist circumference, systolic blood pressure, and diastolic pressure) together have a significant effect of 68,1% with foot skin moisture. The p-value of the Wald test for gender, duration of DM, transient blood glucose, and blood pressure 0,05 so that it can be stated that each the four risk factors of diabetic peripheral neuropathy partially have a significant effect with foot skin moisture. The odds ratio for systolic blood pressure is 1,132, which means that the higher the systolic blood pressure, the 1,312 times will have problems with foot skin moisture. Based on this research, suggested that the puskesmas service unit conduct inspection activities for diabetic peripheral neuropathy risk factors at least every month.